Simultaneous X-ray diffraction, crystallography and fluorescence mapping using the Maia detector - Kirkwood, H.; de Jonge, M.; Muránsky, O.; Hofmann, F.; Howard, D.; Ryan, C.; van Riessen, G.; Rowles, Matthew; Paradowska, A.; Abbey, B. (Pergamon Press, 2018)
© 2017 Acta Materialia Inc. Interactions between neighboring grains influence the macroscale behavior of polycrystalline materials, particularly their deformation behavior, damage initiation and propagation mechanisms. However, mapping all of the critical material properties normally requires that several independent measurements are performed. Here we report the first grain mapping of a polycrystalline foil using a pixelated energy-dispersive X-ray area detector, simultaneously measuring X-ray fluorescence and diffraction with the Maia detector in order to determine grain orientation and estimate lattice strain. These results demonstrate the potential of the next generation of X-ray area detectors for materials characterization. By scanning the incident X-ray energy we investigate these detectors as a complete solution for simultaneously mapping the crystallographic and chemical properties of the sample. The extension of these techniques to broadband X-ray sources is also discussed.